Endobronchial Ultrasound–guided Aspiration of an Endotracheal Bronchogenic Cyst: Case Report and Systematic Review of the Literature. Issue 2 (April 2016) - Maturu, Venkata N.; Dhooria, Sahajal; Agarwal, Ritesh; Behera, Digambar
Abstract : The most common location of bronchogenic cysts is the mediastinum, adjacent to the major airways. Endotracheal bronchogenic cysts are rare and most present in infancy with respiratory failure. Although surgical resection has remained the treatment of choice, there is increasing interest in the management of these cysts with therapeutic aspiration alone. In this article, we describe a 68-year-old man with endotracheal bronchogenic cyst who was managed with endobronchial ultrasound–guided needle aspiration. We also systematically review the literature for reports of endotracheal bronchogenic cysts. The review identified 9 reports (10 patients) with endotracheal bronchogenic cysts. The most common age at presentation was infancy (n=8) and surgical resection was the most common treatment modality used (n=7).